Critical Period Regulation by Thyroid Hormones: Potential Mechanisms and Sex-Specific Aspects - Batista, Gervasio; Hensch, Takao K. (Frontiers in Molecular Neuroscience, 2019)
Adequate perinatal levels of thyroid hormones (THs) are required for normal brain function and development. Studies in non-mammalian species suggest that TH might be involved in the regulation of critical periods (CPs) of heightened plasticity. Yet, it is largely unknown what mechanisms controlling such CPs might be under TH regulation. Here, we briefly review the influence of TH in early life across evolution. We discuss possible links between TH and known circuit and/or molecular mechanisms determining the timing of CPs of heightened brain plasticity. We focus on the role of parvalbumin-positive (PV) interneurons, since their maturation defines CP onset and closure. Specifically, abnormal PV circuits are associated with low perinatal levels of TH, possibly because thyroid hypofunction may increase oxidative stress and/or dysregulate Otx2-mediated maturation of neuroprotective perineuronal nets. In addition, the level of cholinergic transmission is important for CP plasticity. Potentially, TH levels could affect gain changes in cholinergic transmission that can alter brain development. We believe that understanding how TH impacts CPs of circuit refinement will shed light onto the principles underlying normal developmental trajectories. Given that the thyroid gland expresses estrogen and androgen receptors, its activity can potentially be regulated differently between the sexes, contributing to sexually dimorphic behaviors.